Near-field microwave focusing evaluation of dielectric lens antenna for human body model - Amirah Abd Rahman; Kamilia Kamardin; Yoshihide Yamada; Masaharu Takahashi (Institute of Advanced Engineering and Science, 2023)
Various small focus spot applicators are being investigated for hyperthermia therapy, which requires microwave concentration to heat tumors in the human body. Dielectric lens antenna is frequency independent and has strong focusing capability to achieve a very small focusing spot. In this paper, lenses with diameters of 30, 50 and 70 cm were designed to evaluate the size of the focal spot in the human body model. The electromagnetic simulator, FEKO was used to generate rays and near-field focusing data of dielectric lenses at a frequency of 2.45 GHz. The simulated focal spot sizes agreed well with the theoretical values. An analytical investigation into the power at the focal spot was conducted using the proposed power relations of the focused lens novel equation. The theoretical propagation loss is used to represent the power density degradation at the focal spot caused by microwave absorption by the human body. The simulation results of the focused lens in the human body indicated that the 30 cm lens achieved a larger focal spot with a greater focusing power, 0.714 mW compared to the 70 cm lens, which achieved a smaller focal spot but a lower focusing power, which was 0.393 mW.